Standardization of the dosage form for the combined herbal medicine with anti-allergic activity - Kotov, Semen; Gontova, Tetyana (Annals of Mechnikov's Institute, 2022)
Introduction. The creation of a combined herbal preparation with anti-allergic action is an urgent task, it is supported by a wide base of herbal drugs for the creation of the future medicine, a wide range of biologically active substances in their original form, low toxicity and the practical absence of side effects. Such an object is the developed combined plant extract based on the composition of herbal drugs – bur-marigod herb, calendula flowers and hawthorn leaves and flowers - in a ratio of 6:3:1. The aim of the work was to standardize the dosage form of a combined herbal medicine (hard gelatine capsules), to develop methods of their quality control. Materials and methods. The combined herbal preparation of anti-allergic action with a filler of 50% microcrystalline cellulose was developed according to the utility model patent. Samples of capsules containing the combined drug were obtained using a manual capsule machine. The capsule mass was placed in a hard gelatine capsule, size #0, cylindrical in shape with a transparent body and a transparent lid. Study of flowability, bulk density and tapped density of the capsule mass was carried out according to the methods of State Pharmacopeia of Ukraine (SPhU), 2.9.16, 2.9.34. Analytical scales ES225M-DR manufactured by «Preisa Gravimetrics AG», Switzerland and a drying cabinet 2B-151 manufactured by «Odessa Medical Laboratory Technology» were used to determine the loss on drying. Determination of the dissolution of capsules was carried out on a dissolving device for tablets and capsules SOTAX AT-7 (Switzerland). Qualitative analysis was carried out using the method of thin-layer chromatography according to the national monographs of the SPhU "Bur-marigold herb" and "Calendula flowers". As external standards, pharmacopoeial standard samples (caffeic acid, hyperoside, chlorogenic acid, rutin, luteolin, luteolin-7-glycoside, calendulosides), as well as extracts of bur-marigold, calendula, hawthorn and combined dry extract were used. The total content of polyphenolic compounds was determined using a modified Folin–Ciocalteu reactive spectrophotometry method. Pyrogallol was used as a standard sample, which the content of polyphenols was calculated. Validation studies of quantitative determination method were carried out in accordance with the requirements of the general article SPhU 2.4, 5.3.N.2 "Validation of analytical methods and tests". Results & discussion. The loss on drying of the obtained capsule mass was 4.89+0.03% which ensured satisfactory flowability of the capsule mass and its stability during storage. During the study of the technological characteristics of the obtained capsule mass, the following results were obtained: bulk density - 0.571 g/cm3; tapped density - 0.714 g/cm3; compressibility index (Carr Index) – 20%; the Hausner ratio – 1.25; flowability – 11.11 g/s, which met the requirements of the SPhU 2.9.16. 2.9.34. 2.9.36. The identification of capsules was carried out by TLC method, using for this purpose the capsule mass obtained by determining the average mass of the contents of the capsules. When conducting a TLC test in the conditions of the national monograph "Bur-marigold herb" to detect the zones of flavonoids and hydroxycinnamic acids, characteristic zones of the extracts of bur-marigold, calendula and hawthorn were found in the chromatogram of the capsule mass. During the identification of triterpene compounds in the capsule mass under the conditions of Identification method D of the national monograph "Calendula flowers", 2 purple zones were found, which coincided in color and location with the corresponding zones on the chromatogram of the reference standard solution of calendulosides. It was found that the average weight of the capsules was 0.609734 ± 0.0102 g, the deviation from the average weight was in the range from 0.18% to 2.75%, the maximum deviation during the analysis of the tested capsules was 2.75%, which met the requirements of the SPhU, 2.9.5. Determination of dissolution was carried out on a device with a basket, the speed of rotation of the basket - 100 revolutions/min, 500 ml of water was used as a dissolution medium, the temperature of the medium was (37 ± 0.5) °С. 6 capsules were placed in the device, after 45 minutes, 10 ml of the solution was taken from each vessel, filtered, discarding the first 5 ml and then quantitative determination of polyphenols was carried out. As a result, it was found that the amount of active substance released into the dissolution medium within 45 minutes was at least 93% (average for 6 capsules – 96.5%), which met the requirements of the SPhU, 2.9.3. Quantitative determination of polyphenols was carried out by the spectrophotometric method (SPhU, 2.2.25). The development and validation tests were carried out on the capsule mass obtained by determining the content of 20 capsules. During the validation studies, the following metrological characteristics were checked: specificity, linearity, accuracy, precision and intra-laboratory precision. It was found that the method of quantitative determination of polyphenols met the requirements of SPhU 2.4, 5.3.N.2 according to all the studied validation characteristics. The content of total polyphenols in the preparation, in terms of pyrogallol, is regulated to be at least 12 mg in one capsule. Conclusions. The parameters of standardization of the dosage form for the combined herbal medicine with antiallergic activity have been developed. The pharmaco-technological characteristics of the capsule mass and capsules were studied according to the indicators that are mandatory and regulated by the requirements of the SPhU. A complex of physico-chemical methods of analysis has been developed, which allows systematic support for the pharmaceutical development of developed capsules. The validation characteristics of the method for the quantitative determination of polyphenols in accordance with the requirements of the SPhU were studied. Keywords: standardization, combined herbal extract, dosage form, pharmaco-technological characteristics, validation